A comprehensive and comparative study on the action of pentacyclic triterpenoids on Vibrio cholerae biofilms. (December 2020) - Bhattacharya, Sudipta Paul; Bhattacharya, Arijit; Sen, Aparna
Abstract: While serving as environmental reservoir for V. cholerae infection, biofilms are also crucial for intestinal colonization of the pathogen. Triterpenoids, a group of bioactive phytochemicals, have been tested for antibiofilm activity against model biofilm forming bacteria in recent times. In this context, glycyrrhetinic acid (GRA), ursolic acid (UA) and betulinic acid (BA), representing three categorically distinct groups of pentacyclic triterpenoids, are targeted for profiling their impact on Vibrio cholerae C6709 biofilms. The triterpenoids substantially affected biofilm associated attributes like formation, substratum adherence and dispersion from preformed biofilms. Though at variable degree, the compounds decreased cell surface hydrophobicity and composition in terms of macromolecular content. Not only EPS-associated extracellular enzyme activities were estimated to be reduced by triterpenoid exposure, ultra structural analysis also revealed that GRA, UA and BA can affect extracellular polymeric substance (EPS) content. Albeit total extracellular proteolytic activity remained unaffected by the triterpenoids, GRA treatment resulted in considerable reduction of extracellular gelatinase activity. Molecular docking analysis indicated potential interaction with cyclic di-GMP sensor VpsT, autoinducer-2 sensor kinase LuxP-LuxQ and transcriptional activator HapR, components of complex quorum sensing networks modulating biofilm formation. Comprehensive analysis of antibiotic action revealed accentuation of cephalosporin antibiotics with GRA and UA while BA potentiated action of fluoroquinolones against biofilmed bacteria, widening the scope of combinatorial therapeutic strategy. Highlights: Representatives of distinct groups of pentacyclic triterpenoids are profiled for impact on Vibrio cholerae C6709 biofilms. Each of the triterpenoids affected biofilm formation and biofilm associated attributes of the bacteria. The triterpenoids affected extracellular polymeric substances (EPS) and also accentuated action of antibiotics on biofilms. Molecular docking analysis suggested possibilities of interaction with various quorum sensing components of the bacteria.